The reconciliation with nature in Herbert Marcuse and its critique by Martin Seel - Ράντης Kωνσταντίνος (The Greek Review of Social Research, 2013)
The advancing environmental destruction of our planet and, in general, man’s cruel stance towards nature, both external and internal, has brought forcefully their relation back into the center of philosophical criticism. Herbert Marcuse referred extensively to man’s relation to nature in his Counterrevolution and Revolt (1972), where he develops the idea of a reconciliation between the two endorsing, on the one hand, the otherness of nature as the limit of spirit and recognizing, on the other hand, nature as a subject without teleology. Based on a rather aesthetic conception of nature, Martin Seel characterizes man’s relation to it as a regressive ideal of reconciliation, which misrecognizes their constitutive difference. In the place of the dialectic of reason and nature, aiming at the reconciliation of society and nature (Marcuse), there emerges an aesthetic rationality that recognizes and preserves the opposition between culture and nature (Seel).